ATRT-11. MOLECULAR BACKGROUND AND SURVIVAL OF PATIENTS WITH ATRT AND RHABDOID TUMOURS; SINGLE CENTRE EXPERIENCE. (23rd April 2019) - Misove, Adela; Vlckova, Marketa; Zamecnik, Josef; Krskova, Lenka; Vanova, Katerina; Stary, Jan; Malinova, Bela; Pernikova, Ivana; Vicha, Ales; Liby, Petr; Tichy, Michal; Kyncl, Martin; et al.
Abstract: Rhabdoid tumour is a fatal disease that can occur in central nervous system as ATRT or in soft tissues or kidneys. The treatment is challenging because of very young age of such patients and aggressiveness of the disease. We aimed to collect demographic and clinical data of patients treated between 2001 and 2018 at our institution. We evaluated survival, molecular features of the tumours and the incidence of rhabdoid tumour predisposing syndrome (RTPS). During the time period we diagnosed 26 patients with rhabdoid tumors; 19 with ATRT, five with mesenchymal rhabdoid tumour (MRT) (mediastinum, urinary bladder, heart, neck) and two with kidney rhabdoid tumour (KRT). Interestingly, two patients with MRT developed ATRT while still on treatment. One patient with ATRT was diagnosed with urinary bladder MRT 6 years after the primary diagnosis. All three patients were confirmed to harbor germ-line SMARCB1 mutation. RTPS was diagnosed in 27% of our patients and was strongly correlated with development of metachronous rhabdoid tumours. Somatic SMARCB1 mutation and/or exonic/whole gene deletions were detected in all patients. Fifteen out of 19 patients with ATRT were treated with curative intent as per EU-RHAB registry protocol (n=8) or other regimens containing chemotherapy +/- radiation (n=7). 5-year progression-free survival was 26, 7% and 5-year overall survival 31, 2%. Only three long-term survivors recruited from our cohort, all three treated with radiation. Two survivors suffer from severe neurocognitive impairment, whereas the only patient with normal intellectual functioning was treated and irradiated at the age of 15. We can conclude that patients with RTPS need to be surveyed for occurrence of metachronous rhabdoid tumours. Survival of our patients is very poor indicating the urgent need of implementing different treatment strategy.